P58 Genetic, virological and immunological pre-treatment predictors of therapy response to Peg-IFN/ribavirin in children with chronic hepatitis C. (6th September 2011) - Carey, I; Bruce, M; Bansal, S; Tizzard, S; Joshi, D; Vergani, D; Mieli-Vergani, G
Abstract : Introduction: Vertically acquired chronic hepatitis C (CH-C) is a mild disease in childhood but may accelerate in adolescence. Effective early therapy with pegylated interferon (Peg-IFN) and ribavirin (Riba) prevents progressive liver damage. Control of HCV infection depends on both innate and adaptive immunity. Little is known about treatment predictors in children with CH-C. Aim: To assess whether single nucleotide polymorphisms (SNP) near IL28B gene rs12979860 and rs8099917, HCV genotype (G) and pre-treatment innate and adaptive immunity [frequency/phenotype of natural killer (NK) cells, HCV-specific T cell responses, frequency/phenotype of T regulatory cells (T-regs), plasma levels of IFN-γ inducible protein 10 (IP-10)] predict therapy response in children with CH-C. Method: Patients: 32 children with CH-C (19 males, median age 12 yrs, 53% G1) treated according to genotype with Peg-IFN (60 μg/m 2 /week) and riba (15 mg/kg/d) were divided into responders (22, R), relapsers (4, Rel) and non-responders (6, NR). Methods: rs12979860 and rs8099917 were tested by direct sequencing; baseline numbers of NK cells (CD3 - CD56 + ) and their subsets CD56 dim /CD56 bright, CD3 − CD56 +/− CD16 +/−, of CD4+cells expressing programmed death receptor (CD4 + PD1 + ) and of T-regs (CD4 + CD25 + FoxP3 + ) by flowcytometry on peripheral blood mononuclear cells (PBMC). PBMC IFN-γ and IL-10 production after exposure to HCV-core, NS3, NS4, NS5 antigens was evaluated by intracellular cytokine staining. Baseline IP-10 plasma levels [pg/ml] were measured by ELISA. All presented as median. Results: rs12979860 haplotype CC was present in 34% (91% R and 9% NR), CT in 47% (73% R, 7% Rel and 20% NR) and TT in 19% (17% R, 50% Rel and 33% NR); rs8099917 haplotype TT was seen in 50% (88% R and 12% NR), GT in 44% (50% R, 29% Rel and 21% NR) and GG in 6% (50% R and 50% NR) patients. Non-G1 CH-C was linked with better response than G1 (53% vs 80%, p=0.02). Baseline number of CD56 bright NK cells was higher in R than Rel & NR (3.7% vs 1.8% and 1.3%, p=0.05). Compared to R, Rel and NR had higher numbers of CD3 - CD56 - CD16 cells (17.4% vs 12.9% & 10.7%, p=0.05), of HCV-core-specific IL-10 producing cells (CD4 + /IL-10: 4.4% and 3.8% vs 1.7%, p=0.03), of CD4+PD1+ cells (7.1% and 6.9% vs 4.3%, p=0.03) and of T-regs (4.2% and 3.0% vs 1.4%, p=0.04). Baseline plasma IP-10 levels were higher in NR than Rel and R (85 vs 34 and 15, p<0.01). By multivariate analysis only possession of CC rs12979860 and TT rs8099917 haplotypes and low baseline IP-10 levels were associated with response to therapy. Conclusion: Possession of both major haplotypes CC rs12979860 and TT rs8099917 for IL28B gene SNPs and low baseline IP-10 levels predict successful therapy response in children with CH-C.